Effects of Wx Genotype, Nitrogen Fertilization, and Temperature on Rice Grain Quality - Xia, Duo; Wang, Yipei; Shi, Qingyun; Wu, Bian; Yu, Xiaoman; Zhang, Changquan; Li, Yanhua; Fu, Pei; Li, Minqi; Zhang, Qinglu; Liu, Qiaoquan; Gao, Guanjun; et al. (Frontiers in Plant Science, 2022)
Quality is a complex trait that is not only the key determinant of the market value of the rice grain, but is also a major constraint in rice breeding. It is influenced by both genetic and environmental factors. However, the combined effects of genotypes and environmental factors on rice grain quality remain unclear. In this study, we used a three-factor experimental design to examine the grain quality of different Wx genotypes grown under different nitrogen fertilization and temperature conditions during grain development. We found that the three factors contributed differently to taste, appearance, and nutritional quality. Increased Wx function and nitrogen fertilization significantly reduced eating quality, whereas high temperature (HT) had almost no effect. The main effects of temperature on appearance quality and moderate Wx function at low temperatures (LTs) contributed to better appearance, and higher nitrogen fertilization promoted appearance at HTs. With regard to nutritional quality, Wx alleles promoted amylose content (AC) as well as starch-lipids content (SLC); nitrogen fertilization increased storage protein content (PC); and higher temperature increased lipid content but decreased the PC. This study helps to broaden the understanding of the major factors that affect the quality of rice and provides constructive messages for rice quality improvement and the cultivation of high-quality rice varieties.